Efficacy and Safety of Probiotics Combined With Traditional Chinese Medicine for Ulcerative Colitis: A Systematic Review and Meta-Analysis - Hu, Yu; Ye, Zhen; She, Yingqi; Li, Linzhen; Wu, Mingquan; Qin, Kaihua; Li, Yuzheng; He, Haiqing; Hu, Zhipeng; Yang, Maoyi; Lu, Fating; Ye, Qiaobo (Frontiers in Pharmacology, 2022)
Background: The combination of probiotics and traditional Chinese medicine (TCM) is a prospective therapy for ulcerative colitis (UC), and its efficacy and safety need to be urgently evaluated. Objective: This study aims to comprehensively assess the efficacy and safety of probiotics combined with TCM for the treatment of UC. Methods: The Pubmed, EMBASE, Cochrane library, China Academic Journals (CNKI), Wan-fang database, Chinese biomedical literature service system (CBM), and Chinese Science and Technology Journals (CQVIP) were searched. Subgroup analysis were designed in accordance with different control drugs, treatment courses, and types of probiotics. The Review Manager software (version 5.4.1) was utilized for statistical analysis. Results: 14 original studies containing 1154 patients were analyzed and showed that probiotics with TCM was more effective than 5-aminosalicylic acid (5-ASA), probiotics or TCM used individually. Moreover, probiotics combined with TCM could inhibit the intestinal inflammation, reduce the recurrence rate and the incidence of adverse events. The subgroup analysis showed that a mixture of different probiotics was more effective than a single strain. Conclusion: It is suggested that probiotics combined with TCM could effectively control clinical symptoms, inhibit intestinal inflammatory response, and finally slow down the disease progress and reduce the disease recurrence with less adverse events. The mixture of different probiotics used in conjunction with individually tailored TCM is a potential clinical strategy for UC.